Achieving Sustainable Future through Indigenous People: The Case of Weaver Community in South Pringgasela, West Nusa Tenggara - Marinda Putri, Anggina; Kusumastuti, Retno (Hasanuddin Economics and Business Review, 2020)
This article discusses weave fabric as one of the potential industrial development areas in East Lombok, West Nusa Tenggara. The discussion is conducted by looking at indigenous people as resources that need to be maintained. Indigenous people are native people of an area or natives who maintain the indigenous knowledge as local wisdom of the area. Lombok has weave fabric as a valuable cultural heritage. In the beginning, many villages in Lombok developed various kinds of weavings. However, due to the development of each of the villageâ€™s territory, few were able to survive and some had even become extinct due to the declining number of weavers. This is what had led to the establishment of a group of weavers in South Pringgasela. Although in the beginning the establishment of the weaver community was intended to facilitate the weavers in selling their weaving products, the weaver community eventually became a weaving information center for anyone who wants to learn about weaving. This step will achieve success if the surrounding indigenous community were to actively carry it out. A sustainable result is achieved because it is rooted in the weaver community itself. This study employed mixed methods and collected data by using questionnaires, observations and in-depth interviews.Â